2014
DOI: 10.1007/s10029-014-1334-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic embedded absorbable prosthesis for prevention of surgical mesh infection: experimental study in rats

Abstract: Impregnation of the absorbable hydrophilic prosthesis PGA-TMC with cefazolin prevents the infection of the prosthesis placed in infected localization. Therefore, we think this option should be considered as a new and useful alternative in case of contaminated and dirty surgical fields or when a replacement of the prosthesis is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Antimicrobial meshes can be made by dipping/soaking, plasma surface functionalization, plasma-induced graft polymerization [216] (see Figure 3). The antibiotic dipping/soaking method [217][218][219][220], antiseptics [221] and enzymes [222,223] dissolved in a liquid solution (usually aqueous) that are physically adsorbed onto the mesh. This technique, while useful, has not demonstrated clinical superiority over systemic antibiotic therapy.…”
Section: Antimicrobial Meshes and Their Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial meshes can be made by dipping/soaking, plasma surface functionalization, plasma-induced graft polymerization [216] (see Figure 3). The antibiotic dipping/soaking method [217][218][219][220], antiseptics [221] and enzymes [222,223] dissolved in a liquid solution (usually aqueous) that are physically adsorbed onto the mesh. This technique, while useful, has not demonstrated clinical superiority over systemic antibiotic therapy.…”
Section: Antimicrobial Meshes and Their Fabrication Methodsmentioning
confidence: 99%
“…Prior to the clinical translation of these meshes, further studies including long-term evaluation and biocompatibility studies are needed. Other meshes that have already shown an evident decrease in bacterial colonization of the Gram-positive S. aureus are prostheses impregnated with the antibiotic cefazolin [220]. Although adhesions to the prosthesis were produced when it was placed in contact with intra-abdominal viscera, the antibiotic mesh reduced the formation of adhesions compared with the control group, besides inhibiting the inflammatory response to infection [220].…”
Section: Meshes With Antibioticsmentioning
confidence: 99%
“…The loading efficiency was estimated to be around 0.10e0.20 mg/cm 2 of prosthesis, which was sufficient to prevent contamination in an infected rabbit model [81]. Nonspecific physical adsorption of antibiotics [81,88,96,100], antiseptics [103] and enzymes [112,116] were reported by dipping or soaking aqueous solution containing the therapeutics directly on the meshes. Under such condition, the amount of antibacterial compound loaded depends mainly on the fluid adsorption capability of the mesh substrate.…”
Section: Dipping/soakingmentioning
confidence: 99%
“…It was observed that impregnation of the mesh with cefazolin prevents the infection of the prosthesis placed in infected wound [95].…”
Section: Mesh Modificationsmentioning
confidence: 99%